The monocyte-derived cytokine response in whole blood from preterm newborns against sepsis-related bacteria is similar to term newborns and adults - Jans, Jop; van Dun, Sven C. J.; Gorissen, Renske; Pieterman, Roel F. A.; Voskamp, Tess S.; Schoenmakers, Sam; Taal, Hendrik Robert; Unger, Wendy W. J. (Frontiers in Immunology, 2024)
Sepsis is characterized by a dysregulated innate immune response. It is a leading cause of morbidity and mortality in newborns, in particular for newborns that are born premature. Although previous literature indicate that the pro-inflammatory response may be impaired in preterm newborns, serum levels of monocyte-derived cytokines, such as TNF-α and IL-6, vary highly between newborns and can reach adult-like concentrations during sepsis. These contradictory observations and the severe consequences of neonatal sepsis in preterm newborns highlight the need for a better understanding of the pro-inflammatory cytokine response of preterm newborns to improve sepsis-related outcomes. Using an in vitro model with multiple read outs at the transcriptional and protein level, we consistently showed that the monocyte-derived cytokine response induced by sepsis-related bacteria is comparable between preterm newborns, term newborns and adults. We substantiated these findings by employing recombinant Toll-like receptor (TLR) ligands and showed that the activation of specific immune pathways, including the expression of TLRs, is also similar between preterm newborns, term newborns and adults. Importantly, we showed that at birth the production of TNF-α and IL-6 is highly variable between individuals and independent of gestational age. These findings indicate that preterm newborns are equally capable of mounting a pro-inflammatory response against a broad range of bacterial pathogens that is comparable to term newborns and adults. Our results provide a better understanding of the pro-inflammatory response by preterm newborns and could guide the development of interventions that specifically modulate the pro-inflammatory response during sepsis in preterm newborns.